2005
DOI: 10.1002/bjs.4762
|View full text |Cite
|
Sign up to set email alerts
|

Five-year follow-up of a randomized clinical trial of laparoscopic total versus anterior 180° fundoplication

Abstract: Anterior 180 degrees partial fundoplication was as effective as total fundoplication for managing the symptoms of gastro-oesophageal reflux in the longer term. It was associated with a lower incidence of side-effects, although this was offset by a slightly higher risk of recurrent reflux symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
101
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 17 publications
8
101
2
Order By: Relevance
“…35,36 An additional analysis was performed based on the latest follow-up of the three trials that reported outcome at five years and beyond. Outcome at five years and beyond was available for 335 out of 370 [90.5%] patients.…”
Section: Outcome At Five Years and Beyondmentioning
confidence: 99%
“…35,36 An additional analysis was performed based on the latest follow-up of the three trials that reported outcome at five years and beyond. Outcome at five years and beyond was available for 335 out of 370 [90.5%] patients.…”
Section: Outcome At Five Years and Beyondmentioning
confidence: 99%
“…A randomized clinical trial comparing fundoplication techniques found better postoperative functional data for the 180° anterior than for a total Nissen wrap [8]. On the other hand, a reduced reflux control was expected for the long-time course [8,9]. None of these studies used standardized questionnaires for evaluation of postoperative quality of life (QoL).…”
Section: Introductionmentioning
confidence: 99%
“…Anterior partial fundoplication is an alternative approach, and randomised trials have also shown that these techniques also reduce the risk of wind related side effects, as well as consistently reducing the risk of post-fundoplication dysphagia 4,5,6,7 …”
Section: Introductionmentioning
confidence: 99%